2013
DOI: 10.1051/0004-6361/201220620
|View full text |Cite
|
Sign up to set email alerts
|

Damping of kink waves by mode coupling

Abstract: Context. Recent observations of the corona reveal ubiquitous transverse velocity perturbations that undergo strong damping as they propagate. These can be understood in terms of propagating kink waves that undergo mode coupling in inhomogeneous regions. Aims. The use of these propagating waves as a seismological tool for the investigation of the solar corona depends upon an accurate understanding of how the mode coupling behaviour is determined by local plasma parameters. Our previous work suggests the exponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
116
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(126 citation statements)
references
References 45 publications
10
116
0
Order By: Relevance
“…But, it has been shown that in some cases a Gaussian decay is more appropriate [12,32]. Physical mechanisms responsible for the Gaussian damping of slow magnetoacoustic waves in the corona have not been identified yet, but are known in the case of coronal fast magnetoacoustic waves of the kink symmetry [44].…”
Section: Decaying Harmonic Qppmentioning
confidence: 99%
“…But, it has been shown that in some cases a Gaussian decay is more appropriate [12,32]. Physical mechanisms responsible for the Gaussian damping of slow magnetoacoustic waves in the corona have not been identified yet, but are known in the case of coronal fast magnetoacoustic waves of the kink symmetry [44].…”
Section: Decaying Harmonic Qppmentioning
confidence: 99%
“…Based on numerical (Pascoe et al 2012) and analytical investigations (Hood et al 2013) of mode coupling, Pascoe et al (2013a) described how the damping of kink oscillations by mode coupling can exhibit two different regimes. A Gaussian damping profile applies for early times, and an exponential damping profile at later times.…”
Section: Introductionmentioning
confidence: 99%
“…Pascoe et al (2016b) examined the damping profile of standing kink oscillations observed by SDO/AIA and found examples of both Gaussian and exponential damping behaviour. Pascoe et al (2013a) proposed that a unique seismological inversion for the transverse density profile would be possible in cases of oscillations for which both regimes were observed. This method was recently applied to three coronal loops by Pascoe et al (2016a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integro-differential equation for the continuous variation in amplitude with height z can be approximated by Gaussian and exponential functions at small and large z, respectively. This was employed by Pascoe et al (2013) who produced a simpler, piecewise spatial damping profile suitable for use for seismological inversions. The initial stage of the damping envelope is described by a Gaussian function,…”
Section: Introductionmentioning
confidence: 99%